A multi-wavelength speciation framework for high-temperature hydrocarbon pyrolysis. (March 2019) - Pinkowski, Nicolas H.; Ding, Yiming; Johnson, Sarah E.; Wang, Yu; Parise, Thomas C.; Davidson, David F.; Hanson, Ronald K.
Highlights: Multi-wavelength speciation methods for high-temperature pyrolysis in shock tubes. Review of fixed-wavelength, high-temperature laser absorption diagnostics for jet fuel fragments. Database of high temperature absorption cross-section measurements. Abstract: A framework for the study of high-temperature hydrocarbon pyrolysis is presented. The proposed framework details a multi-wavelength speciation method using convex optimization, a review of complementary fixed-wavelength laser diagnostics, and a database of high-temperature absorption cross-sections to enable use of the framework for 11 different species. The proposed speciation method involves a vectorized Beer-Lambert system solved under solution constraints using convex optimization. In support of the proposed method, a review of pertinent laser diagnostics and a database of high-temperature absorption cross-sections are also provided. The database includes measured absorption cross-sections of methane (CH4 ), ethylene (C2 H4 ), propene (C3 H6 ), isobutene (i-C4 H8 ), 1-butene (1-C4 H8 ), benzene (C6 H6 ), toluene (C7 H8 ), and four jet fuels (samples of Jet A, JP5, JP8, and Gevo ATJ) at the wavelengths of 3.1758 µm, 3.17595 µm, 3.283 µm, 3.392 µm, 3.410 µm, 10.532 µm, 10.675 µm, 10.89 µm, 10.958 µm, 10.962 µm, and 11.345 µm within the range of 300–1600 K and 0.25–4 atm. The database is comprised of over 1000 high–temperature absorption cross-section measurements from new shock tube experiments, new Fourier transform infrared spectrometer (FTIR) experiments, and an aggregated dataset from the literature. The convex speciation method and cross-section database provided will facilitate laser absorption studies of hydrocarbon pyrolysis used in the development of chemical kinetic mechanisms.